Efecto de la fertilización edáfica en el crecimiento y desarrollo de Phaseolus vulgaris cv. ICA Cerinza - Bautista Zamora, Daniel Mauricio; Chavarro Rodriguez, Carmen Lorena; Cáceres Zambrano, Jeimmy; Buitrago Mora, Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 122-132.